Enlightenment Fundamentals: Rights, Responsibilities & Republicanism (Diametros, 2014)
This essay re-examines some key fundamentals of the Enlightenment regarding individual rights, responsibilities and republicanism which deserve and require re-emphasis today, insofar as they underscore the character and fundamental importance of mature judgment, and how developing and fostering mature judgment is a fundamental aim of education. These fundamentals have been clouded or eroded by various recent developments, including mis-guided educational policy and not a little scholarly bickering. Clarity about these fundamentals is more important today than ever. Sapere aude!